2017
DOI: 10.1186/s13098-017-0220-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of variable antidiabetic treatments strategy on oxidative stress markers in obese patients with T2DM

Abstract: AimTo evaluate the effect of different anti-diabetic treatment strategy on oxidative stress markers in patients with type 2 diabetes mellitus (T2DM).Subject and methodsA total of 93 patients with T2DM treated with metformin (G1 = 25), OHA (G2 = 22), OA and insulin (G3 = 26) and insulin alone (G4 = 20). In all patients, lipid profile and glycemic indices were assessed using routine laboratory tests. MDA and Oxidized LDL were assessed using commercially available ELISA kits. Laboratory tests were performed at ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Again, we hypothesize that some hypoglycemic agents may not prevent oxidative changes by normalization of hyperglycemia but rather serve as a possible trigger for marked lipid peroxidation in a controlled diabetic state. Our assumptions are supported by a previous study where it was demonstrated that, in T2DM induction of oxidative stress is largely influenced not only by hyperglycemia but also by the various classes of antidiabetic therapeutic agents [20].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Again, we hypothesize that some hypoglycemic agents may not prevent oxidative changes by normalization of hyperglycemia but rather serve as a possible trigger for marked lipid peroxidation in a controlled diabetic state. Our assumptions are supported by a previous study where it was demonstrated that, in T2DM induction of oxidative stress is largely influenced not only by hyperglycemia but also by the various classes of antidiabetic therapeutic agents [20].…”
Section: Discussionsupporting
confidence: 86%
“…However, the mechanism through which the anti-diabetic agents subject patients to oxidative stress is currently unknown. However, a recent report demonstrated that induction of oxidative stress in T2DM is not influenced solitarily by hyperglycemia but also by the categories of anti-diabetic drugs [20]. Our data, therefore, suggest that hypoglycemic agent (metformin) is associated with oxidative stress in the same way with chronic hyperglycemia; hence, glycemic…”
Section: Resultsmentioning
confidence: 43%
“…Furthermore, GV was significantly associated with an oxidative stress marker 5. Monnier et al 3 and Abeer et al 26 also reported that GV correlated with an oxidative stress marker in patients with DM. In the present study, ox-LDLc, an oxidative stress marker was significantly greater in the higher MAGE group.…”
Section: Discussionmentioning
confidence: 87%
“…Type 2 diabetes (T2DM) has been shown to account for over 90% of all cases of diabetes mellitus and is commonly associated with a myriad of metabolic consequenc-Int J Diabetes Metab 2019;25:118-126 DOI: 10.1159/000500912 es including dyslipidemia, hypertension, metabolic syndrome, and atherosclerosis [1]. Chronic hyperglycemia associated with T2DM induces increased generation of free radicals such as reactive oxygen species (ROS), and the accruing oxidative stress has been described as the major pathophysiologic factor linking the progression of T2DM and associated complications [2]. Increased ROS production in T2DM has also been linked to hyperinsulinemia and impaired insulin action, thus forming a vicious cycle [3].…”
Section: Introductionmentioning
confidence: 99%
“…Hyperglycemia and hyperketonemia also accruing from an insulin deficiency in T2DM have been associated with electrolyte imbalance [7]. Improved glycemic control has been associated with a reduction in these metabolic complications in T2DM [2].…”
Section: Introductionmentioning
confidence: 99%